Strategy For Developing a Slum-Free City With a Sustainability Approach in Dili, Timor Leste - Rosa Amaral Vong (Riviera Publishing, 2026)
The rapid population growth and increasing demand for residential areas in Dili City, Timor-Leste, have led to the emergence of slum settlements, particularly in the Tasitolu area, which faces environmental, social, and economic pressures. This study aims to analyze the slum conditions in Tasitolu and formulate strategies for a slum-free Dili City using a sustainability-based approach. A mixed-methods approach was employed, collecting primary data through field surveys and interviews, and secondary data from planning documents and statistical reports. The analysis used seven indicators from the Kota Tanpa Kumuh (KOTAKU) model: building conditions, roads, water access, drainage, wastewater management, solid waste management, and fire protection. These indicators were grouped into social, economic, and environmental sustainability aspects. Results showed critical issues in the environmental and economic aspects, with relatively better conditions in the social aspect. Development strategies include in-situ upgrading, limited relocation, strengthening local economic activities, and enhancing government capacity in spatial planning and control. A phased roadmap of short-, medium-, and long-term actions is proposed to achieve a sustainable, slum-free Dili City.